Alternative Approaches for Efficient Inhibition of Hepatitis C Virus RNA Replication by Small Interfering RNAs - Krönke, Jan (American Society for Microbiology, 2004)
Persistent infection with hepatitis C virus (HCV) is a leading cause of chronic hepatitis, liver cirrhosis, and hepatocellular carcinoma. It has recently been shown that HCV RNA replication is susceptible to small interfering RNAs (siRNAs), but the antiviral activity of siRNAs depends very much on their complementarity to the target sequence. Thus, the high degree of sequence diversity between different HCV genotypes and the rapid evolution of new quasispecies is a major problem in the development of siRNA-based gene therapies. For this study, we developed two alternative strategies to overcome these obstacles. In one approach, we used endoribonuclease-prepared siRNAs (esiRNAs) to simultaneously target multiple sites of the viral genome. We show that esiRNAs directed against various regions of the HCV coding sequence as well as the 5′ nontranslated region (5′ NTR) efficiently block the replication of subgenomic and genomic HCV replicons. In an alternative approach, we generated pseudotyped retroviruses encoding short hairpin RNAs (shRNAs). A total of 12 shRNAs, most of them targeting highly conserved sequence motifs within the 5′ NTR or the early core coding region, were analyzed for their antiviral activities. After the transduction of Huh-7 cells containing a subgenomic HCV replicon, we found that all shRNAs targeting sequences in domain IV or nearby coding sequences blocked viral replication. In contrast, only one of seven shRNAs targeting sequences in domain II or III had a similar degree of antiviral activity, indicating that large sections of the NTRs are resistant to RNA interference. Moreover, we show that naive Huh-7 cells that stably expressed certain 5′ NTR-specific shRNAs were largely resistant to a challenge with HCV replicons. These results demonstrate that the retroviral transduction of HCV-specific shRNAs provides a new possibility for antiviral intervention.